Introduction to mathematical modeling and computer simulations - Mityushev, Vladimir V.; Nawalaniec, Wojciech; Rylko, Natalia (CRC Press, Taylor & Francis Group, 2018)
Introduction to Mathematical Modeling and Computer Simulations is written as a textbook for readers who want to understand the main principles of Modeling and Simulations in settings that are important for the applications, without using the profound mathematical tools required by most advanced texts. It can be particularly useful for applied mathematicians and engineers who are just beginning their careers. The goal of this book is to outline Mathematical Modeling using simple mathematical descriptions, making it accessible for first- and second-year students.